Stimulus-induced repetitive discharge in F-wave measurement in nerve conduction studies - OGURI, Masayoshi; IMAI, Chitose; NOGAMI, Satoru; ADACHI, Yoshiyuki; MOTOKURA, Toru; FUKUDA, Tetsuya; SATOU, Akemi; TAKAMORI, Toshihiro (Japanese Journal of Medical Technology, 2019)
Stimulus-induced repetitive discharge (SIRD) is one of the abnormal responses recorded after M-waves with the exception of F-waves. There is no consensus on the clinical significance and developmental mechanism of SIRD, and it is not specific to any disease. Here, we studied the clinical significance of SIRD by accumulating cases in which abnormal responses other than F-waves (non-F-waves) were recorded after M-waves. Non-F-waves were found in 80 (28.1%) of the 284 subjects who underwent nerve conduction studies (NCSs). Among them, 30 (10.6%) had uniform waveforms. Then, we classified non-F-waves on the basis of periodicity. Uniform and periodic non F-waves were found in five diabetes patients, two amyotrophic lateral sclerosis patients, one Isaac syndrome patient, and one Parkinson’s disease patient. Uniform and periodic non-F-waves were frequently detected in the same nerve found to be abnormal in motor NCSs compared with the nonperiodic ones. On the other hand, nonuniform non-F-waves were frequently observed in diseases with involuntary movements and can be artificially elicited by voluntary muscle contraction, so caution is advised when considering it as SIRD. Uniform and periodic non-F-waves correspond to SIRD and reflect some kind of neurological dysfunction, and the use of SIRD for clinical evaluation warrants future studies. However, artifacts may be mixed in the late component of the M-waves, so it is necessary to be prudent in reading non-F-waves.